2013
DOI: 10.1128/iai.01383-12
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of the Leptin Receptor Q223R Polymorphism on the Host Transcriptome following Infection with Entamoeba histolytica

Abstract: dResistance to amebiasis is associated with a polymorphism in the leptin receptor. Previous studies demonstrated that humans with the ancestral Q223 leptin receptor allele were nearly four times less likely to be infected with Entamoeba histolytica than those carrying the mutant R223 allele. We hypothesized that the Q223 allele protected against E. histolytica via STAT3-mediated transcription of genes required for mucosal immunity. To test this, mice containing the humanized LEPR Q or R allele at codon 223 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
(102 reference statements)
0
21
0
Order By: Relevance
“…The mouse model of an E. histolytica cecal infection was used to determine the differences between Q223 and R223 mice early during an infection. Previous work had shown that by 12 h after infection a difference could be observed in infection rates between Q223 and R223 mice, with complete eradication in Q223 but not R223 mice by 72 h ( 11 ). This 12-h time point was therefore chosen to investigate the very early host processes that could account for the differences in phenotypes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The mouse model of an E. histolytica cecal infection was used to determine the differences between Q223 and R223 mice early during an infection. Previous work had shown that by 12 h after infection a difference could be observed in infection rates between Q223 and R223 mice, with complete eradication in Q223 but not R223 mice by 72 h ( 11 ). This 12-h time point was therefore chosen to investigate the very early host processes that could account for the differences in phenotypes.…”
Section: Resultsmentioning
confidence: 97%
“…The rapid divergence of infection phenotypes observed, with full eradication of infection by 72 h in mice with the ancestral Q223 leptin receptor allele ( 11 ), suggested that the innate immune system was responsible for the differences in infection clearance. R223 mice were observed to have a reduced neutrophil population in the lamina propria compared to Q223 mice 12 h after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Samples (total 24, 6 mice per group) from mice that received two inoculations of L. plantarum or two inoculations of pbs/bsa diluent prior to virus or vehicle only challenge and harvested on day 19 were processed further for DNA microarray analysis. RNA extraction and target preparation were performed as described (Mackey-Lawrence et al, 2013) for all samples except RNA was extracted using RNeasy 96 well kit (Qiagen, Valencia, CA). Hybridization, fluidics and scanning were performed according to standard Affymetrix protocols (http://www.affymetrix.com) with the whole mouse genome 430 2.0 chip within the Genomics Unit of the Research Technologies Section (NIAID).…”
Section: Methodsmentioning
confidence: 99%
“…RNA quality was determined using 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA) and the Agilent RNA 6000 Pico kit. RNA was quantitated by RT-QPCR as described in Mackey-Lawrence et al, 2013 (21). The lowest RNA yield of 0.9 ng was from 654 cells.…”
Section: Methodsmentioning
confidence: 99%